Asuhan Keperawatan Medikal Bedah Pada Pasien Ny.Y Dengan Diabetes Melitus Tipe Ii Di Ruangan Muzdalifah Rumah Sakit Aisyiyah Pariaman 2026 - Iga Mawar; Linda Marni; Aulia Asman; Kheniva Diah Anggita (CV. ITTC INDONESIA, 2026)
Type II diabetes mellitus is a non-communicable disease characterized by increased blood glucose levels (hy perglycemia) due to impaired insulin secretion and resistance. According to the World Health Organization (WHO), the number of diabetes sufferers is estimated to reach 783 million in 2030 and increase to 830 million in 2045. In Indonesia, the prevalence of Type II Diabetes Mellitus with cases reached 1.63 million, while West Sumatra was 1.8% with a total of 3.7 million cases. At Aisyiyah Pariaman Hospital, Type II DM ranks 3rd with a total of 247 cases. The purpose of this study is to understand and apply nursing care to patients with Type II DM. This study uses a case study research method. This study was conducted in the Muzdalifah inpatient room of Aisyiyah Pariaman Hospital on February 1014, 2026. The results of Mrs. Y's research found nursing problems, namely unstable blood glucose levels, acute pain, risk of nutritional deficits, activity intolerance, and sleep pattern disorders. The interventions and implementation included glucose monitoring, pain management, nutrition and fluid monitoring, support for independent daily activities, and sleep support. Based on the five-day evaluation, the patient's condition was resolved. The patient was advised to adopt a healthy lifestyle, a low-sugar and low-fat diet, regular exercise, regular check-ups, and adherence to medication.